Loss of NQO1 generates genotoxic estrogen-DNA adducts in Fuchs Endothelial Corneal Dystrophy - Miyajima, Taiga (Free Radic Biol Med, 2019)
Fuchs Endothelial Corneal Dystrophy (FECD) is an age-related genetically complex disease characterized by increased oxidative DNA damage and progressive degeneration of corneal endothelial cells (HCEnCs). FECD has a greater incidence and advanced phenotype in women, suggesting a possible role of hormones in the sex-driven differences seen in the disease pathogenesis. In this study, catechol estrogen (4-OHE(2)), the byproduct of estrogen metabolism, induced genotoxic estrogen-DNA adducts formation, macromolecular DNA damage, and apoptotic cell death in HCEnCs; these findings were potentiated by menadione (MN)-mediated reactive oxygen species (ROS). Expression of NQO1, a key enzyme that neutralizes reactive estrogen metabolites, was downregulated in FECD, indicating HCEnC susceptibility to reactive estrogen metabolism in FECD. NQO1 deficiency in vitro exacerbated the estrogen-DNA adduct formation and loss of cell viability, which was rescued by the supplementation of N-acetylcysteine, a ROS scavenger. Notably, overexpression of NQO1 in HCEnCs treated with MN and 4-OHE(2) quenched the ROS formation, thereby reducing the DNA damage and endothelial cell loss. This study signifies a pivotal role for NQO1 in mitigating the macromolecular oxidative DNA damage arising from the interplay between intracellular ROS and impaired endogenous estrogen metabolism in post-mitotic ocular tissue cells. A dysfunctional Nrf2-NQO1 axis in FECD renders HCEnCs susceptible to catechol estrogens and estrogen-DNA adducts formation. This novel study highlights the potential role of NQO1-mediated estrogen metabolite genotoxicity in explaining the higher incidence of FECD in females.